A Software Tool for Cognitive Work Analysis. (September 2017) - Hingu, Dharmendra Praving; Muthukrishnan, Somasundaram; Rantanen, Esa M.; Lintern, Gavan
Cognitive Work Analysis (CWA) is a conceptual framework that allows for analysis of all factors that affect human-system interactions. The products of this system of analyses can then be directly transformed into design requirements for information systems. Doing CWA by hand is quite tedious, however, and larger projects where data are collected from multiple individuals doing the same task differently, or when multiple different tasks are included in a larger-scale CWA, pose special challenges. It is apparent that streamlined documentation and support tool for CWA is needed. Even at a cost of some lost flexibility, the benefits of a software tool to support data collection are apparent. The tool should also support the analyses of large amounts of data from multiple operators within a large system, where individual differences in ways of doing things are expected. This paper describes the development of such a tool with examples of its use.